Ultrafast reproducible synthesis of a Ag-nanocluster@MOF composite and its superior visible-photocatalytic activity in batch and in continuous flow. Issue 28 (12th July 2021) - Arenas-Vivo, Ana; Rojas, Sara; Ocaña, Iván; Torres, Ana; Liras, Marta; Salles, Fabrice; Arenas-Esteban, Daniel; Bals, Sara; Ávila, David; Horcajada, Patricia
Abstract : Ultrafast synthesis of a robust Ag-nanocluster metal–organic framework composite with superior photocatalytic performances, even working under continuous flow in the removal of emerging contaminants from water. Abstract : The (photo)catalytic properties of metal–organic frameworks (MOFs) can be enhanced by post-synthetic inclusion of metallic species in their porosity. Due to their extraordinarily high surface area and well defined porous structure, MOFs can be used for the stabilization of metal nanoparticles with adjustable size within their porosity. Originally, we present here an optimized ultrafast photoreduction protocol for the in situ synthesis of tiny and monodisperse silver nanoclusters (AgNCs) homogeneously supported on a photoactive porous titanium carboxylate MIL-125-NH2 MOF. The strong metal–framework interaction between –NH2 and Ag atoms influences the AgNC growth, leading to the surfactant-free efficient catalyst AgNC@MIL-125-NH2 with improved visible light absorption. The potential use of AgNC@MIL-125-NH2 was further tested in challenging applications: (i) the photodegradation of the emerging organic contaminants (EOCs) methylene blue (MB-dye) and sulfamethazine (SMT-antibiotic) in water treatment, and (ii) the catalytic hydrogenation of p -nitroaniline (4-NA) to p -phenylenediamine (PPD) with industrial interest. It is noteworthy that compared with the pristine MIL-125-NH2, the composite presents an improved catalytic activity and stability, being able to photodegrade 92% of MB in 60 min and 96% of SMT in 30 min, and transform 100% of 4-NA to PPD in 30 min. Aside from these very good results, this study describes for the first time the use of a MOF in a visible light continuous flow reactor for wastewater treatment. With only 10 mg of AgNC@MIL-125-NH2, high SMT removal efficiency over 70% is maintained after >2 h under water flow conditions found in real wastewater treatment plants, signaling a future real application of MOFs in water remediation.